2015
DOI: 10.1371/journal.pgen.1005378
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Age and Sex on Genetic Associations with Adult Body Size and Shape: A Large-Scale Genome-Wide Interaction Study

Abstract: Genome-wide association studies (GWAS) have identified more than 100 genetic variants contributing to BMI, a measure of body size, or waist-to-hip ratio (adjusted for BMI, WHRadjBMI), a measure of body shape. Body size and shape change as people grow older and these changes differ substantially between men and women. To systematically screen for age- and/or sex-specific effects of genetic variants on BMI and WHRadjBMI, we performed meta-analyses of 114 studies (up to 320,485 individuals of European descent) wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
305
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(333 citation statements)
references
References 92 publications
18
305
0
3
Order By: Relevance
“…In agreement with this, a larger fraction of the variance in fat distribution to different compartments could also be attributed to the SNPs investigated in women, as compared to men. These results are consistent with previous GWAS that have revealed sexual dimorphisms in genetic loci for adiposityrelated phenotypes, such as waist-circumference, waist-to-hip ratio, and visceral fat mass [14,[30][31][32]. In our study we find evidence for 43 loci whose effects differed between the males and females, of which one overlapped with a locus (LYPLAL1) that has previously been reported to display a different effect between sexes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with this, a larger fraction of the variance in fat distribution to different compartments could also be attributed to the SNPs investigated in women, as compared to men. These results are consistent with previous GWAS that have revealed sexual dimorphisms in genetic loci for adiposityrelated phenotypes, such as waist-circumference, waist-to-hip ratio, and visceral fat mass [14,[30][31][32]. In our study we find evidence for 43 loci whose effects differed between the males and females, of which one overlapped with a locus (LYPLAL1) that has previously been reported to display a different effect between sexes.…”
Section: Discussionsupporting
confidence: 93%
“…In our study we find evidence for 43 loci whose effects differed between the males and females, of which one overlapped with a locus (LYPLAL1) that has previously been reported to display a different effect between sexes. Our lead SNP (rs1415287) at the LYPLAL1 locus is in strong LD with rs2820443 and rs4846567 (R 2 =1.00 and 0.99), which have been associated with stronger effects on WHR and WHR adjusted for BMI in women [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this does not appear to be the case in most studies. For example, in one recent report POMC was not among 100 QTLs that were identified or confirmed in a population of over 320,000 individuals (Winkler et al 2015). Voisin et al (2015) have reported that methylation of a single nucleotide polymorphism within the POMC promoter region was among methylation site variants from 28 genes associated with obesity.…”
Section: Heterozygous Effectsmentioning
confidence: 99%
“…Currently, the only way this issue is handled is by scaling up sample size. For example, human Genome-Wide Association Studies (GWAS) now typically recruit tens of thousands of individuals in a hunt for small-effect variants [2][3][4]. Practically, however, cohort size cannot be infinitely increased.…”
Section: Introductionmentioning
confidence: 99%